Bridging the digital divide: analyzing public participation in Indonesia's e-government through the e-participation index - Nurhidayat, Nurhidayat; Nurmandi, Achmad; Congge, Umar (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
This study explores the level of public participation in e-government in Indonesia, focusing on the Electronic Participation Index (EPI). This research uses qualitative methods and qualitative content analysis. The main data was obtained from the UN E-Government Knowledgebase, especially the E-Participation Index for 2016 to 2022 and Indonesia's E-Participation Index ranking data from 2004 to 2022. The results of this study show that the improvement of e-government infrastructure and services has not been fully successful in increasing public participation. The challenges faced include inadequate regulations, lack of data integration, gaps in ICT infrastructure, and inequality in internet access, especially in rural areas. The culture of bureaucracy, corruption, collusion, and nepotism also hinder public trust in the e-government system. Some government initiatives, such as the Peduli Lindungi application, have shown positive results but have not been fully optimal. To overcome these challenges, it is necessary to improve regulations, integrate data, reduce the digital divide, and increase government transparency and accountability. What is new about this study lies in its comprehensive analysis of the E-Participation Index in the Indonesian context, which provides a unique perspective on the correlation between e-government infrastructure and public participation levels. In addition, the study offers actionable insights and recommendations for policymakers to improve e-government services by addressing specific regional and cultural barriers.